EFISIENSI TEKNIS BANK DEVISA NASIONAL DARI SEGI BIAYA DENGAN MENGUNAKAN METODE NON PARAMETRIK: DATA ENVELOPMENT ANALYSIS/DEA - Rinaldi Rustam (Universitas Trisakti, 2005)
This Research conducted by using the data of 76 Bank Devisa Nasional, These banks report the data to the Central Bank relatively more complete than that of other banks and they have variative input- output structure. Bank Devisa Asing & Campuran are excluded from this study because it considered that the capital structure and fiancé of them are still closely related to headquater in overseas. The result of the study, Shours that before The economic crisis there are 45 banks which have relatively hight efficiency score (100%), and 27 Bank Devisa Nasional have efficiency score under 100%, After the economic crisis the efficiency score is declined, proved by the fact that only 27 Bank devisa Nasional which have 100 % score efficiency, and 42 Banks experianced. The 30 % declining efficiency score. While 22 banks remain stable. Nevertheles, 8 Banks increase efficiency score during The economic crisis, named BTN, Panin, Bira, SGP,,Namura, Hastin.. comparing the empirical result of this study by using DEA/Non parametric with the previous study/parametric by using the similar data, we come up with the conclusion that both approach yielded the relatively similar result. In the other word, this study support the previous research by Andreas Resti, Bergemo (1997).